Deterministic Double Dose Vaccination Model of COVID-19 Transmission Dynamics - Optimal Control Strategies with Cost-Effectiveness Analysis - Abidemi, Afeez; Fatmawati; Peter, Olumuyiwa James (The Indonesian Bio-Mathematical Society, 2024)
In this study, we propose a deterministic double dose vaccination model of COVID-19 transmission dynamics optimal control with cost-effectiveness analysis. It is imperative for decision-makers and the government to prioritize the application of preventive and control measures for COVID-19 based on efficiency and costbenefit analysis. This is pivotal in resource-constrained regions where the disease is endemic. Thus, this work is mainly devoted with the development and analysis of an optimal control for COVID-19 dynamics with five timevarying functions; first dose vaccination, second dose vaccination, personal protection, testing or screening, and treatment. The model is qualitatively analysed with the overall goal to minimize the spread of COVID-19 and the costs related to control implementation with the aid of optimal control theory. The effect of adopting each control intervention in each of the three distinct groups which are created by classifying all conceivable combinations of at least three control interventions is demonstrated through the numerical simulations of the optimality system. Using the average cost-effectiveness ratio and incremental cost-effectiveness ratio techniques, the most economical control intervention is determined for each group. The study reveals that when the resources are readily available, application of the strategy that combines optimal first dose vaccination, personal protection, screening or testing and treatment is as efficient as implementing all the five optimal control interventions simultaneously as they both avert the same number of infections. However, in resource-limited communities when joint implementation of only three interventions is possible, the strategy combining personal protection, testing or screening and treatment is strongly recommended. Out of all the intervention options being considered, this strategy is also affirmed to be the most cost-effective overall. Economic evaluation of the control intervention strategies further suggests that combination of first dose vaccination, second dose vaccination, testing or screening and treatment is the most cost-effective strategy when implementation of only four interventions is strictly allowed.